Pemanfaatan Media Ibadah Di Masjid Shirotol Mustaqim, Waru, Pamekasan: (Studi Kasus: Penggunaan Media Ibadah oleh Kiyai Muadi Arif) - Jalaluddin, Moh; Rahman, Nailur; Sunawati, Sunawati (Jurnal Pengabdian Masyarakat dan Penelitian Thawalib, 2023)
The purpose of this study is to find out and describe the use of da'wah media in worship. This research method uses a qualitative method with a case study design. Data collection techniques: interviews, observation, documentation. Data management: reduction, data presentation, drawing conclusions. Data validation techniques: triangulation of sources and techniques. The results of the research show: (1) worship activities: congregational prayers, recitation, tadarus, dhikr, taklim assemblies, and other educational activities. (2) worship media: (a) yellow book: the book of safinatunnajah which contains the science of fiqh (the foundations of Islam) and the book of nashohibul ibad about the science of tasawuf. (b) loudspeakers: for the call to prayer, recitation, and religious lecture activities. (c) Digital Clock: to indicate the time of prayer and other worship. (d) supporting Al-Qur'an: to put the Al-Qur'an when reciting. (d) charity box: to store money from donations (charity) of the community. Conclusion: the media for worship at the mosque has been used very well. The best suggestion: mosque managers add other media such as special sandals for ablution, a place to store prayer rugs and mukenah.